2000
DOI: 10.1046/j.1460-9568.2000.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell mRNA expression of HCN1 correlates with a fast gating phenotype of hyperpolarization‐activated cyclic nucleotide‐gated ion channels (Ih) in central neurons

Abstract: Hyperpolarization-activated currents (Ih) are key players in shaping rhythmic neuronal activity. Although candidate genes for Ih channels have been cloned (HCN1-HCN4), the subunit composition of different native Ih channels is unknown. We used a combined patch-clamp and qualitative single-cell reverse transcription multiplex polymerase chain reaction (RT-mPCR) approach to analyse HCN1-4 coexpression profiles in four neuronal populations in mouse CNS. Coexpression of HCN2, HCN3 and HCN4 mRNA was detected in sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
122
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 28 publications
19
122
0
3
Order By: Relevance
“…The underlying molecular differences remain to be defined. Qualitative single-cell RT-mPCR experiments have shown that DA SN neurons coexpress three of the four I h channel subunits, HCN2, HCN3, and HCN4 (Franz et al, 2000). However, the molecular composition of native neuronal I h channels that might exist as homomeric or heteromeric complexes (Chen et al, 2001;Ulens and Tytgat, 2001;Yu et al, 2001) as well as the possible differential I h channel subunit expression between different DA subpopulations remains unclear.…”
Section: Functional Diversity Of Anatomically and Neurochemically Idementioning
confidence: 99%
“…The underlying molecular differences remain to be defined. Qualitative single-cell RT-mPCR experiments have shown that DA SN neurons coexpress three of the four I h channel subunits, HCN2, HCN3, and HCN4 (Franz et al, 2000). However, the molecular composition of native neuronal I h channels that might exist as homomeric or heteromeric complexes (Chen et al, 2001;Ulens and Tytgat, 2001;Yu et al, 2001) as well as the possible differential I h channel subunit expression between different DA subpopulations remains unclear.…”
Section: Functional Diversity Of Anatomically and Neurochemically Idementioning
confidence: 99%
“…This would predict that the contribution of I h to resting membrane potential and resistance (Lee and Ishida, 2007) and to rebound excitation (Tabata and Ishida, 1996;Lee et al, 2003;Lee and Ishida, 2007) is increased by conditions that elevate intracellular cAMP levels (Vaquero et al, 2001;Nir et al, 2002;Dunn et al, 2006;Mills et al 2007). However, properties of the net current are shaped by the presence of other HCN isoforms (Franz et al, 2000;Santoro et al, 2000;Altomare et al, 2001;Chen et al, 2001). It would therefore be natural for future studies to test the possibility that HCN4 channels co-localize with other HCN channels in retinal ganglion cells.…”
Section: Presence Of Camp-sensitive Channels In Ganglion Cellsmentioning
confidence: 99%
“…Of the four characterized genes encoding HCN channels, two (HCN1 and 2) are substantially expressed in rodent hippocampus (Bender et al, 2001;Moosmang et al, 1999;Santoro et al, 2000) and both isoforms can reside in a single neuron (Brewster et al, 2002;Franz et al, 2000). HCN4 is expressed almost exclusively in subcortical regions, whereas levels of HCN3 expression within neurons are generally low (Bender et al, 2001;Moosmang et al, 1999;Santoro et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Because the isoform composition of both homomeric and heteromeric HCN channels determines their physiological characteristics (Robinson and Siegelbaum, 2003;Santoro and Baram, 2003), the relative abundance of the HCN isoforms, as well as the degree to which heteromerization occurs, will contribute to the properties of the I h of an individual neuron (Franz et al, 2000;Santoro et al, 2000;Vasilyev and Barish, 2002), and thus to its intrinsic firing patterns and network responses. Differential regulation of HCN1 and HCN2 mRNA expression has been found in pathological states (Bender et al, 2003;Bräuer et al, 2001;Brewster et al, 2002), including experimental febrile and kainate-induced seizures, and has been associated with altered properties of the I h (Chen et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%